Stochastic model for nmr analysis of multicomponent solutions of biologically active aromatic molecules - Evstigneev, M. P.; Evstigneev, V. P.; Shokurov, M. V. (Biophysical Bulletin, 2005)
A mathematical description of the N-component mixture of interacting aromatic molecules in an aqueous solution has been suggested with a possibility to compute the observed NMR proton chemical shift for each of the dissolved molecular components (N-STOCH model). On the basis of the N-STOCH model, a computer algorithm for the calculation of dynamic equilibrium in the multicomponent mixture has been developed and validated against the three-component mixture of antibiotic daunomycin, vitamin B2, and caffeine.